About Learning, Memory, and Neural Circuits: An Approaching to the Cognitive Processes in Living Systems - Alvarez Toro, Edgardo Orozimbo (2010)
Learning can be considered a fundamental evolutionary advance to those living systems that acquired this capacity during the early evolution of life. Perception of an environment that has past and present permitted primitive animals to acquire a more complete vision of the surrounding world. The cognitive use of information that is permanently available to the living system is now recognized as "memory." Although many years have passed, and many researchers are deeply involved in the study of learning and memory, still its intricate nature is not completely understood. A review of common terms used in memory research such as, memory, learning, and trial are discussed and redefined in a more restricted form with the intention of reaching a common consensus. The most accepted model of learning is presented in a diagram of a "learning unit," and a unifying concept of a "vector memory engram unit" for learning and storing of memory is also discussed. Finally, implications of the model are considered in the context of diseases that produce memory deficits in order to compare the predictions of the model with the behavioural evidence from patients with lesions in restricted brain zones.